DECONSTRUCTING CULTURAL STEREOTYPES TO UNCOVER HIDDEN TOURISM POTENTIALS - Dwi Rini Sovia Firdaus; Layung Paramesti Martha; Sardi Duryatmo (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
People of Minangkabau descent in Indonesia have several negative stereotypes that have long developed in society. Not only can it disturb the psychological condition of these ethnic group members, but it can also trigger intercultural conflict. This condition does not help the local government promote West Sumatra as a cultural tourism destination. This study deconstructs the negative stereotypes in order to correct misperceptions that have occurred so far. The study tests Hofstede’s cultural dimensions in two ways; first is towards the deconstruction process of Minangkabau’s original traditional teachings. The second is towards the nuclear family configuration using ANOVA test to find the shifting cultural values. This study attempts to find the origin of the negative stereotypes and confirm it with the original traditional teachings. This study can ward off bad cultural stereotypes as it corrects misconceptions about the nature of the matrilineal Minangkabau culture. Besides elaborating on the cause of negative stereotypes, this study also finds out the origin of positive ones. They are known to have high social awareness, strong entrepreneurial abilities, and excellent leadership skills. Thanks to these three good stereotypes, the Minangkabau people can then produce crafts that are intelligent and timeless, such as the production of engravings on songket cloth that are full of philosophy, the architectural feature of the Bagonjong house roof, the traditional dress, culinary menus, music, and art. This research produces data artifacts about contemporary Minangkabau culture to benefit the cultural tourism industry. This deconstruction approach has never been tested on the Minangkabau tribe.